Delineation and Fine‐Scale Structure of Fault Zones Activated During the 2014–2024 Unrest at the Campi Flegrei Caldera (Southern Italy) From High‐Precision Earthquake Locations - Francesco Scotto di Uccio; Anthony Lomax; Jacopo Natale; Titouan Muzellec; Gaetano Festa; Sahar Nazeri; Vincenzo Convertito; Antonella Bobbio; Claudio Strumia; Aldo Zollo (Geophysical Research Letters)
Abstract In the past two decades, the central portion of Campi Flegrei caldera has experienced ground uplift up to 15 mm/month, with an increase of rate, magnitude and extent of the seismicity. In this work, we perform multi‐scale precise earthquake relocation of the 2014–2024 seismicity, mapping in detail activated fault zones. We relate the geometry, extent, and depth of these zones with up‐to‐date structural reconstructions of the caldera. The current seismicity is mainly driven by ground‐uplift‐induced stress concentration on pre‐existing, weaker fault zones, some of which identified for the first time. These structures are not only related to the inner caldera and dome resurgence but also to volcano‐tectonic events of the last 10 ka. The extent of imaged fault segments suggests they can accommodate ruptures up to a moment magnitude 5.1, significantly increasing seismic hazard in the area.